Can Macroinvertebrate Traits Be Explored and Applied in Biomonitoring Riverine Systems Draining Forested Catchments? - Edegbene, Augustine O.; Arimoro, Francis O.; Odume, Oghenekaro N.; Ogidiaka, Efe; Keke, Unique N. (Frontiers in Water, 2021)
Trait-based approach (TBA) in recent time have received tremendous attention as complementary tool over taxonomic-based approach in assessing ecological health of riverine systems in developed countries, but in the Afrotropical region the trait-based approach is still in its infancy. No trait-based approach has been developed for riverine systems draining forested catchment in the Afrotropical region. Hence, this study was conducted to explore macroinvertebrates traits as potential biomonitoring tools in assessing ecological health of riverine systems draining forested catchments in the Niger Delta area of Nigeria. Selected physico-chemical variables were sampled together with macroinvertebrates in 18 stations of 10 riverine systems for a period spanning 2008 to 2012. The 18 stations were classified into three ecological classes namely near natural stations (NNS), slightly disturbed stations (SDS) and moderately disturbed stations (MDS) using physico-chemical-based classification with the aid of principal component analysis (PCA). The results revealed traits such as possessions of hardshell body armouring, preferences for clear and transparent water and opaque water, climbing and crawling mobility mechanisms, large (>20-40 mm) body size, preferences for scrapping, shredding and grazing feeding habits to be associated with NNS and SDS based on RLQ analysis performed. Also, traits such as tegument/cutaneous respiration, soft and exposed body armouring, burrowing mobility mechanism, spherical body shape, preference for detritus (FPOM) food materials, small (>5-10 mm) body size and preference for filter feeding mechanism were associated with MDS. A further fourth-corner test performed revealed tegument/cutaneous respiration preference, soft and exposed body armouring and burrowing mobility mode, which were associated with the MDS on the RLQ ordination were also positively correlated to BOD5; while preference for clear and transparent water, which were positively associated with MDS, were also positively correlated with pH and negatively correlated to DO. Overall, this study affirmed that (TBA) can be explored in biomonitoring riverine systems draining forested catchments.